Comparison of the Efficacy and Safety between Generic Intravenous Omeprazole (zefxon®) and Original Omeprazole (losecspi®) in the Adjunct Treatment of Non-Variceal Upper Gastrointestinal Bleeding in Siriraj Hospital - Darin Lohsiriwat (2018)
Background: Clinical efficacy and safety of generic omeprazole have not been well studied in Thailand. Objective: Determine whether generic omeprazole (Zefxon®) is inferior to original omeprazole (Losec®) in the treatment of non-variceal upper gastrointestinal bleeding (UGIB) in Siriraj Hospital. Material and Method: Medical records of adult patients with the diagnosis of non-variceal UGIB receiving intravenous omeprazole (either Zefxon® or Losec®) in Siriraj Hospital between January 2006 and September 2010 were reviewed. Noninferiority study was used to investigate whether the generic omeprazole was no more than 10% less effective than the original omeprazole. The primary end points were recurrent bleeding and mortality within seven and 30 days. Surgery, endoscopic retreatment, blood transfusions, length of hospital stay and safety were also analyzed. Results: Of 200 randomly selected patients in each group, there was no difference in age, gender, co-morbidities, severity of UGIB, endoscopic findings and endoscopic intervention between patients receiving generic omeprazole and original omeprazole. Overall rate of recurrent bleeding, mortality, and surgical intervention within 30 days were 12.3%, 5.5% and 2.0%, respectively. The rates of recurrent bleeding, overall mortality, and non-variceal UGIB related mortality within seven and 30 days were not significantly different between the two groups. Neither were the rates of endoscopic retreatment and surgery. The incidence of adverse side effects was 3.5% in each group. Cox regression analysis showed no significant association between type of omeprazole and recurrent bleeding or mortality. Compared to the original omeprazole, the hazard ratio of recurrent bleeding, overall mortality, and non-variceal UGIB related mortality in patients receiving generic omeprazole was 1.44 (95% CI 0.82-2.53; p = 0.21), 2.12 (95% CI 0.90-5.43; p = 0.08) and 1.82 (95% CI 0.53-6.21; p = 0.34), respectively. Conclusion: Although the original omeprazole Losec® tended to have more favorable outcomes in the treatment of non-variceal UGIB in the present study, non-inferiority test showed that the efficacy and safety of the generic omeprazole Zefxon® was not inferior to those of the original omeprazole.